DRY NEEDLING CAN BE AN ALTERNATIVE TREATMENT FOR HEMIFACIAL SPASM - Marisdina, Selly; Sugiharto, Henry; Pradian, A (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Back Ground: Hemifacial spasm is one of movement disorder case that commonly found in daily clinical practice. Epidemiological data are very limited, the average prevalence is 11 per 100,000 population, 14.5 per 100,000 in women and 7.4 per 100,000 in men. In Germany, the estimated prevalence is 8000 to 9000 peoples.1 The incidence of women is more than that of men with a ratio of 2:1. Based on Yaltho and Jankovic study in 2011, out of 215 patients, the ratio of men to women was 1:1.8.2 One study in Indonesia also reported that most of the subjects were female (64.7%).3 Treatment with botulinum toxin injections is preferred to microvascular decompression surgery therapy, but this injection is only effective in a few months and quite expensive. This study is the first study to assess the effectiveness of dry needling on clinical improvement of hemifacial spasm compared to standard therapy of botulinum toxin injection.Methods: The study design was quasi experimental. Total of 24 subjects were divided into two groups. The first group underwent dry needling intervention while the other had botulinum injection. Clinical severity before and after treatment in both groups was assessed using Jankovic and HFS7 scores.Results: In dry needling group there were significant differences between Jankovic and HFS7 score at baseline and at week 1, 2, 3 and 4. While in botox group significant differences were also Jankovic and HFS7 score at baseline and at weeks 2 and 4. There were also a significant difference of Jankovic and HFS7 score when we compared dry needling group to botulinum toxin group.Conclusion: Dry needling can be an alternative treatment for hemifacial spasm, although clinical improvements based on Jankovic and HFS7 scores in dry needling group were not as effective as those with botulinum toxin injections.